The integrated stress response induces R-loops and hinders replication fork progression - Josephine Ann Mun Yee Choo; Schloesser, Denise; Manzini, Valentina; Magerhans, Anna; Dobbelstein, Matthias (bioRxiv, 2020)
The integrated stress response (ISR) allows cells to rapidly shut down most of their protein synthesis in response to protein misfolding, amino acid deficiency, or virus infection. These stresses trigger the phosphorylation of the translation initiation factor eIF2alpha, which prevents the initiation of translation. Here we show that triggering the ISR drastically reduces the progression of DNA replication forks within one hour, thus flanking the shutdown of protein synthesis with immediate inhibition of DNA synthesis. DNA replication is restored by compounds that inhibit eIF2alpha kinases or re-activate eIF2alpha. Mechanistically, the translational shutdown blocks histone synthesis, promoting the formation of DNA:RNA hybrids (R-loops) which interfere with DNA replication. Histone depletion alone induces R-loops and compromises DNA replication. Conversely, histone overexpression or R-loop removal by RNaseH1 each restores DNA replication in the context of ISR and histone depletion. In conclusion, the ISR rapidly stalls DNA synthesis through histone deficiency and R-loop formation. We propose that this shutdown mechanism prevents potentially detrimental DNA replication in the face of cellular stresses.